ANTUSIASME MAHASISWA DALAM PELAKSANAAN PELATIHAN PEMBERDAYAAN KARUNIA ROH DI SEKOLAH TINGGI TEOLOGI KRISTUS ALFA OMEGA SEMARANG PROGRAM STUDI TEOLOGI - Elesabet Elesabet; Chandra Kirana Luhur; Rudyanto Chandra Saputra (JOURNAL of THEOLOGICAL STUDENTS, 2021)
To be able to obtain the gift of the Holy Spirit, everyone, especially God's servants, must have an attitude of enthusiasm to be empowered with the gift of the Holy Spirit. This study aims to describe, photograph the enthusiasm of students in the implementation of the spiritual gift empowerment training that has been carried out at STT Christ Alfa Omega Semarang, especially students of the Theology study program. In this study, researchers used quantitative methods. The methodology used in this research is descriptive quantitative. Based on data analysis, it is known that the level of enthusiasm of students in the implementation of the training to empower the gift of the Holy Spirit at STT Christ Alfa Omega Semarang is in the very good category, which is 84%.